If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -1) = 2x + 2 Reorder the terms: 3(-1 + y) = 2x + 2 (-1 * 3 + y * 3) = 2x + 2 (-3 + 3y) = 2x + 2 Reorder the terms: -3 + 3y = 2 + 2x Solving -3 + 3y = 2 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = 2 + 3 + 2x Combine like terms: -3 + 3 = 0 0 + 3y = 2 + 3 + 2x 3y = 2 + 3 + 2x Combine like terms: 2 + 3 = 5 3y = 5 + 2x Divide each side by '3'. y = 1.666666667 + 0.6666666667x Simplifying y = 1.666666667 + 0.6666666667x
| 39=-6(4n-3) | | w-5=5w-7 | | 24-3h=30 | | 3(y+1)=2x+3 | | (3a-7)-2(a+1)=5 | | 3(x+1)3=24 | | (x*40)+(x*15)=70000 | | 282/344 | | 2x(15)=30x | | 7(8-n)+8n=57 | | (1/7)^4x=343 | | -5x-13=-2+8(6x-8) | | x/64=15/100 | | =4a+16-(a-4) | | 3x+(25)+2x+(115)=180 | | -18+15= | | -39+7n=-4+7(4-8n) | | 9x+(-11)+5x+(17)=90 | | 6x+(12)+3x+(-34)=41 | | 4x-7+x=90 | | 8.5-1.2x=6.7 | | 4(3x+1)-15=5(3x-1) | | 8x-10y=-51 | | 8x-10y=-5 | | y5/3=1 | | y-1/10=5 | | 32x-2+3x-1=12 | | 9x+26+7x-17=(-3x)+5x | | x-0.5x=18000 | | 2(3y+5)=3(5y+.3) | | x-.50x=18000 | | Log(9)4x-log(9)8=2 |